Investigation on responses and capacity of offshore pipelines subjected to submarine landslides. (December 2021) - Fu, Cuiwei; Nian, Tingkai; Guo, Xingsen; Gu, Zhongde; Zheng, Defeng
Highlights: The equivalent boundary conditions are proposed in the developed finite element model for accurately and efficiently capturing pipeline performance under the impact of submarine landslides. The normalized critical impact force of offshore pipelines is reasonably formulated as a function of the normalized landslide width, normalized axial and lateral soil resistances. The design charts are achieved for directly predicting the critical impact force of offshore pipelines and evaluating the pipeline safety under the impact of submarine landslides. Abstract: Offshore pipelines are the main means for transmitting marine oil and gas resources, and they are usually threatened by various geohazards, typically by submarine landslides. However, systematical analyses and solutions for pipeline capacity to resist submarine landslides have been rarely reported. This paper aims to carry out a series of numerical simulations to investigate the responses and capacity of offshore pipelines subjected to submarine landslides. First, a finite element model is developed and validated, in which the pipeline is modeled using beam elements and pipe-soil interaction is modeled using the axial and lateral soil springs with different force-displacement relationships. To further accurately and efficiently assess pipeline performance under the impact of submarine landslides, equivalent boundary conditions are proposed based on the analytical solution. After validation of the equivalent boundary conditions, a series of parametric studies is performed to investigate the capacity of offshore pipelines under the impact of submarine landslides (i.e., critical impact force). Various ranges of soil properties, pipeline burial depths, diameters, steel grades and landslide widths are included in the parametric study. Then through regression and dimensional analysis, the normalized critical impact force is reasonably formulated using the normalized landslide width, normalized axial and lateral soil resistances. Moreover, scour effect induced by seabed currents on the critical impact force is also investigated. Finally, the design charts are achieved and are directly used to predict the critical impact force and evaluate the pipeline safety under the impact of submarine landslides.